Messages from the Inside. The Dynamic Environment that Favors Intestinal Homeostasis - Chieppa, Marcello; Eri, Rajaraman (Frontiers in Immunology, 2013)
An organism is defined as “an individual living thing capable of responding to stimuli, growing, reproducing, and maintaining homeostasis”. Early during evolution multicellular organisms explored the advantages of a symbiotic life. Mammals harbor a complex aggregate of microorganisms (called microbiota) that includes bacteria, fungi and archaea. Some of these bacteria have already defined beneficial roles for the human host that include the ability to break-down nutrients that could not otherwise be digested, preventing the growth of harmful species, as well as the ability to produce vitamins or hormones. It is intuitive that along the evolutionary path several mechanisms favored bacteria that provided advantages to the host which, in return, avoided launching an aggressive immunological response against them. The intestinal immunological response does not ignore the lumenal content, on the contrary, immune surveillance is favored by continuous antigen sampling. Some intestinal epithelial cells are crucial during the sampling process, others actively participate in the defense mechanism. In essence the epithelium acts as a traffic light, communicating to the inside world whether conditions are safe or dangerous, and thus influencing immunological response. In this review we will discuss the dynamic factors that act on the intestinal epithelial cells and how they directly or indirectly influence immune cells during states of health and disease.